PENERAPAN SISTEM PENGAMANAN BERBASIS DESA ADAT (SIPANDU BERADAT) DI DESA ADAT UNDISAN KELOD BANGLI - I Dewa Gede Dwi Permana (Kerta Dyatmika, 2022)
Another problem with traditional Sipandu is that the facilities and infrastructure for protecting the environment are still not being met due to the budget problems that have been explained previously and have an impact on the procurement of facilities and infrastructure. Based on the background of the problem as stated above, several problems can be formulated, including efforts made in implementing a traditional village-based security system (Sipandu Beradat) in the Undisan Kelod Traditional Village and obstacles in implementing a traditional village-based security system (Sipandu Beradat) in the Village. Kelod Undisan Customs. The research method used in this research is empirical juridical. This type of empirical juridical research is research that examines and analyzes the operation of law in society (law in action). The main data used is data sourced from the field. The conclusion in this research is that the efforts made to implement a traditional village-based security system (Sipandu Beradat) in the Undisan Kelod Traditional Village carried out Flexible and Modular Training where this is still one of the options that can be implemented to overcome previous obstacles. Obstacles in implementing a traditional village-based security system (Sipandu Beradat) in the Undisan Kelod Traditional Village: Limited Resources and Training Facilities where adequate education and training requires sufficient facilities and resources, including competent teaching staff, relevant training materials, and infrastructure training.